PENGARUH JUMLAH PENDUDUK TERHADAP JUMLAH KEMISKINAN DI KALIMANTAN BARAT - Yuliansyah Yuliansyah (Cross-border, 2021)
Poverty is still a topic of discussion among the people. The facts show that economic development has not been able to reduce poverty. The purpose of this study is to see the effect of population on poverty levels in West Kalimantan in the 2018-2020 period. In this study using simple linear regression analysis, using panel data with the dependent variable is the number of poor people and the independent variable is the population. The results of this study show that the population has a significant positive effect on the number of poor people in West Kalimantan in the 2018-2020 period.